(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Density function theory with LSDA/3-21G basis set is used to investigate the optimization parameters such as (angles and bonds) and some electronic properties include (cohesive energy, energy gap and lattice constant) of AlSb at nano diamantine and different size of(Linear, Ring, Diamantine and Tetramantine). The results of the present work show that the angles of AlSbH nano molecule in range (96,21-126.05 Å) are near to standard angle of diamond (109.47 Å). Therefore, it is found that the cohesive energy for molecules of studied in decrease state with increase size but the energy gap decreased in gradually shape from (5.2-2.1eV) with increase of the number of atoms, that typical is on the lattice constant. It is finally shown that the size molecules has direct effect on electronic properties to material studied that can used this material in different applications and according to the purpose asked for